2003
DOI: 10.1038/sj.bjc.6600912
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion to the extracellular matrix protein fibronectin modulates radiation-dependent G2 phase arrest involving integrin-linked kinase (ILK) and glycogen synthase kinase-3β (GSK-3β) in vitro

Abstract: Cell adhesion to extracellular matrix (ECM) is thought to confer resistance against cell-damaging agents, that is, drugs and radiation, in tumour and normal cells in vitro. The dependence of cell survival on b1-integrin-linked kinase (ILK), protein kinase Ba/Akt (PKBa/Akt) and glycogen synthase kinase-3b (GSK-3b) activity, which participate in b1-integrin signalling and cell cycle progression was investigated as a function of radiation exposure. Colony-formation assays on polystyrene, fibronectin (FN), laminin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 47 publications
5
46
1
Order By: Relevance
“…Cell division is a highly regulated process that is modulated in response to adverse conditions including ionizing radiation [40,41]. Signaling via adhesion of integrins to laminin 5 is known to be involved in progression through the G1 phase of the cell cycle [32,33,42] and other integrin/ligand interactions in the G2/M transition [35,43]. Our data support adhesion-mediated regulation of the G2 phase through the integrin ligand laminin 5.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Cell division is a highly regulated process that is modulated in response to adverse conditions including ionizing radiation [40,41]. Signaling via adhesion of integrins to laminin 5 is known to be involved in progression through the G1 phase of the cell cycle [32,33,42] and other integrin/ligand interactions in the G2/M transition [35,43]. Our data support adhesion-mediated regulation of the G2 phase through the integrin ligand laminin 5.…”
Section: Discussionsupporting
confidence: 73%
“…G1 phase and S phase [34] are influenced by integrins and it has been recently shown that adhesion of cells to fibronectin through integrin receptors plays a role in regulating the G2 phase and entry into mitosis [35,36]. Signaling events through cell adhesion to laminin 5 through the α6β4 integrin may affect cell cycle regulation after DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…ILK is the binding partner of integrin, associating with the cytoplasmic domain of integrin b1 and mediating integrin-dependent cell attachment (Hannigan et al, 1996). Inhibition of ILK activity or expression results in the inhibition of cell adhesion by its downstream signaling to protein kinase B/Akt and glycogen synthase kinase-3b (Cordes and van Beuningen, 2003;Hannigan et al, 2005)…”
Section: Discussionmentioning
confidence: 99%
“…The nonradioactive Akt kinase assay kit purchased from New England Biolabs GmbH (Frankfurt a.M., Germany) was modified to detect ILK kinase activity as described previously (Cordes and van Beuningen, 2003).…”
Section: Ilk Kinase Assaymentioning
confidence: 99%
“…In great similarity to adherent growing cells (Zhang et al, 2002;Cordes and van Beuningen, 2003;Seidler et al, 2005), these events confer resistance to genotoxic agents such as ionizing radiation or drugs like bleomycin, etoposide or fludarabine.…”
Section: Introductionmentioning
confidence: 99%